2022
DOI: 10.3390/ijms23116207
|View full text |Cite
|
Sign up to set email alerts
|

The Valence Band Structure of the [Ni(Salen)] Complex: An Ultraviolet, Soft X-ray and Resonant Photoemission Spectroscopy Study

Abstract: The valence band photoemission (VB PE) spectra of the [Ni(Salen)] molecular complex were measured by ultraviolet, soft X-ray and resonant photoemission (ResPE) using photons with energies ranging from 21.2 eV to 860 eV. It was found that the Ni 3d atomic orbitals’ (AOs) contributions are most significant for molecular orbitals (MOs), which are responsible for the low-energy PE band at a binding energy of 3.8 eV in the VB PE spectra. In turn, the PE bands in the binding energies range of 8–16 eV are due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This finding is explained by an increase in the effective charges of carbon and nitrogen atoms and a corresponding decrease in the effective charge of oxygen atoms in the ligand during the formation of the [Ni(Salen)] complex. An equally interesting result was obtained in the work [53], where VB PE spectra of the molecular complex [Ni(Salen)] were measured using ultraviolet, soft X-ray, and resonance photoemission methods using photons with energies from 21.2 to 848 eV. As a result, it was established that electronic states at a binding energy of 3.8 eV are associated specifically with the Ni 3d-derived MOs of the complex (see Figure 8).…”
Section: Vb Pesmentioning
confidence: 68%
See 2 more Smart Citations
“…This finding is explained by an increase in the effective charges of carbon and nitrogen atoms and a corresponding decrease in the effective charge of oxygen atoms in the ligand during the formation of the [Ni(Salen)] complex. An equally interesting result was obtained in the work [53], where VB PE spectra of the molecular complex [Ni(Salen)] were measured using ultraviolet, soft X-ray, and resonance photoemission methods using photons with energies from 21.2 to 848 eV. As a result, it was established that electronic states at a binding energy of 3.8 eV are associated specifically with the Ni 3d-derived MOs of the complex (see Figure 8).…”
Section: Vb Pesmentioning
confidence: 68%
“…As noted above in this review, studies of occupied electronic states of the valence band for monomers [M(Salen)] and their polymers using valence photoemission (VB PE) have so far been limited to a few works [45,46,53]. These works are devoted to studying the electronic structure of only the H 2 (Salen) molecule and the [Ni(Salen)] complex.…”
Section: Vb Pesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are normalized to the intensity of the PE band d and plotted on the scale of the valence electron BE’s relative to the Fermi level ( E F ). A preliminary discussion of these spectra was carried out in the framework of a study devoted to a consideration of the structural evolution of the VB PE spectra of the [Ni(Salen)] complex with a change in the energy of its exciting photons in the range of 21.2–848.0 eV [ 34 ]. Here, the qualitative results of this discussion are supplemented with a detailed comparative analysis of the UV PE spectra of H 2 (Salen) and [Ni(Salen)], using the results of the DFT calculations of their valence bands.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that combined studies based on NEXAFS, CL, and VB PES measurements are very effective in characterizing the electronic properties and chemical bonding of similar complexes of nickel porphyrins and phthalocyanine [ 28 , 29 , 30 , 31 , 32 ]. Recently, similar studies have been carried out for the molecular complex [Ni(Salen)], in order to derive information about the features of its local electronic structure [ 33 , 34 ]. As a result, for the [Ni(Salen)] monomer, new knowledge of the energy positions and AO composition of the valence MOs responsible for its high-lying occupied and low-lying vacant electronic states has been obtained.…”
Section: Introductionmentioning
confidence: 99%